MultiCultural Center Grand Opening [excerpts], January 20, 1994 (1994)
Excerpt of VHS videotape, containing footage of the 1994 MCC Grand Opening, including dances by Ballet Folklorico, Grupo Folklorico Imagen y Espritu, and the Chinese Student Association, a ribbon cutting ceremony, and a drum blessing ceremony. The original tape is 43 minutes long, and contains the following content: 0:00:00 The Staff preparing for the Grand Opening of the MCC 0:00:15 The Imagen y Espritu Ballet Folklrico de Cal Poly begins performing 0:03:16 The performance ends and the crowd applauds 0:03:36 An MC welcomes a Cal Poly group of students to perform a traditional Mexican cultural dance 0:03:54 The same group performs another traditional dance 0:06:43 The second performance ends and the crowd applauds 0:06:52 An emcee presents both Cal Poly groups that performed, and thanks the crowd 0:07:31 Both groups exit the stage 0:07:42 The MCC Coordinator announces the next group and gives background of the given traditional Mexican dance 0:08:53 Ballet Folklorico de Cal Poly walks on stage 0:09:13 An MC introduces the group and gives detail that they will be performing five different dances 0:09:58 The music begins to play and the group starts to perform 0:12:23 The first performance is over and the crowd applauds 0:12:40 The second performance begins 0:14:47 The second performance is over and the crowd applauds 0:14:53 The third performance begins 0:17:02 The third performance is over and the crowd applauds 0:17:09 The fourth performance begins 0:19:36 The fourth performance ends and the crowd applauds 0:19:43 The final performance begins 0:22:16 The final performance ends and the crowd applauds 0:22:21 Chinese lion dance begins 0:23:41 The MCC Coordinator announces the ribbon cutting in the University Union 0:24:00 Students start to walk up to the second floor of the University Union to watch the ribbon cutting 0:24:13 There is a balloon archway and a large ribbon in front of the new MCC 0:24:24 The traditional Mexican dances walk into the second floor of the UU 0:24:31 The Lion dancers perform as they enter the second floor of the UU 0:24:58 The MCC Coordinator welcomes everyone to the Grand Opening 0:25:17 The MCC Coordinator announces that the Ethnic Studies minor just passed 0:25:31 Ken Barkley begins speaking about the new MCC 0:26:14 Ken Barkley introduces Dr. Robert Koob 0:26:31 Dr. Robert Koob declares the MCC as officially open 0:26:53 Dr. Robert Koob cuts the ribbon 0:27:05 The MCC Coordinator introduces a traditional African performance 0:27:34 The performer explains and demonstrates the African tradition in honor of the MCC 0:28:38 Two performers begin to drum to signify the traditional African performance 0:30:38 The performer informs the audience of the performance's importance 0:31:35 The traditional African performers begin drumming again 0:31:44 The audience starts chanting with the drumming 0:32:20 People are conversing as some enter the MCC 0:30:40 Students are in the MCC talking with one another, while enjoying food and beverages 0:36:34 The MCC has pictures on the walls displaying aspects from different cultures 0:38:50 People are conversing with one another, while enjoying the new MCC